Feeding Practices in NC-based Early Head Start Programs among Teachers Serving 12-36mo Children - Bullard, Caitlin Elizabeth (East Carolina University, 2019)
Background: Food behaviors are developed during the first few years of life making caregiver interactions especially important in the formation of healthy food preferences. Limited data exists on caregiver feeding styles and practices who work directly with toddlers 12-36 months. Of particular interest are differences in feeding practices among different ethnicities. Objective: To determine feeding styles of Early Head Start (EHS) teachers in North Carolina (NC) and examine differences in feeding practices by ethnicity. Design: Cross sectional data surveying the feeding practices of EHS teachers Participants/Setting: NC-based EHS teachers recruited throughout the state of NC aged 42.81 ± 12.74 working with toddlers 12-36 months. Main outcome measures: Validated instruments, Caregiver Feeding Style Questionnaire (CFSQ) and Mealtime Verbal Comments Checklist Statistical Analyses: Fisher's Exact Test, Mann-Whitney U Test, Pearson's [chi]^2, and Independent t-tests test were used to determine variations between ethnicities of childcare providers who completed the survey. Results: Teachers were categorized as authoritative (17.19%), authoritarian (34.38%), indulgent (29.69), and uninvolved (18.75%). Feeding styles were not significantly different among African Americans (AA) and White (p=0.33) teachers. However, significant differences were observed between individual items in the CFSQ such as "physically struggle with the child to get him or her to eat" (White [mu]=35.93 and AA [mu]=28.09; p=0.02). Statistical significant differences were also observed between 4 items in the Verbal Comments Checklist such as "when you're playing with your cup, you're showing me you're done" (p=0.045). White teachers were more likely to use both supportive (42.5±6.35) and unsupportive (57.48±6.34) comments during mealtime compared to AA with a mean of 37.24±12.69 for supportive comments and 62.76±12.69 unsupportive comments. Conclusions: Additional research is needed to explore direct observations of teacher-toddler interactions during mealtime to understand ethnic differences between teacher feeding styles.
Keywords: Feeding Styles; Ethnicity; Toddlers; Early Head Start Program; Feeding Styles; Educational Personnel; Early Intervention (Education); Child; Feeding Behavior